RANCANG BANGUN MESIN PULPER KOPI MENGGUNAKAN PENGGERAK MOTOR LISTRIK - Tri Ego Wiranata; Ruzita Sumiati; Rakiman Rakiman; Yuli Yetri (The University of Lampung, 2021)
Design and manufacture of coffee pulper machines have been carried out with the aim of completing the needs of the coffee farmer groups when harvesting in the Kayu Aro area, Kerinci. The steps in designing and manufacturing a coffee pulper begins with a literature study, design and calculation, the process of making the tool and ends with testing the tool. Engineering drawing design is done by modeling in SolidWorks software. Coffee peeler machine with a capacity of 4 kg/min, with a machine size of 730 mm x 320 mm x 1040 mm, using an electric motor 1 HP 1420 rpm, with a frame using an elbow profile 40 mm x 40 mm x 3 mm. The transmission system uses an electric motor with an initial rotation of 1420 rpm to 364.6 rpm. In the 2 pulley component D = 74.6 mm and 290.5 mm, V-belt type B No.52, 1 solid shaft D = 25 mm. Initial test results using 2–5 kg of wet coffee beans take 30.07–77.20 seconds, and the skin has separated from the beans cleanly. These results show that the engine capacity is 235.62 kg/h, so that the desired target is met with relatively low operating costs. The existence of this tool will be able to help the process of separating the skin and coffee beans, so that the quality of coffee production will increase. Keywords: coffee, coffee machine, design and construction, farmer groups